Klasifikasi Jenis Buah-Buahan Menggunakan Citra Digital Dengan Metode Convolutional Neural Networks - Yuwan Jumaryadi; Alif Muhammad Ihsan; Bagus Priambodo (STMIK Budi Darma, 2023)
The impact of the COVID-19 pandemic has been felt in changes in consumption patterns. Society and consumption patterns are inseparable, greatly people's consumption patterns that increase during the pandemic are fruits. Fruits are foods rich in vitamins that the body needs to build immunity during this pandemic. Types of fruits are grouped into 2, namely dried fruits and fleshy fruits. To make it easier for consumers to find out the image data of these types of fruit using the CNN method. Convolutional Neural Network is a deep learning algorithm designed to process data in two-dimensional form, for example images or sounds. Based on the classification results that have been carried out obtained values, namely Precision of 94% and 85%, Recall of 85% and 95%, F1-score of 90%, Macro Average of 90%, and Weighted Average of 90%, Weighted Average of 90%.